Identifying Priority Giant Anteater (Myrmecophaga tridactyla) Populations for Conservation in São Paulo State, Brazil - Sartori, Ricardo Quiterio [UNESP]; Lopes, Alessandro Garcia [UNESP]; Aires, Luiz Paulo Nogueira; Bianchi, Rita de Cassia [UNESP]; de Mattos, Cinara Cássia Brandão; Morales, Adriana Coletto [UNESP]; Castiglioni, Lilian [UNESP] (Wiley, 2021)
Habitat loss is the main threat to biodiversity conservation worldwide. Some species may be particularly susceptible to the effects of fragmentation and the isolation of populations. The impacts of human activity on wild animal populations may be understood through relationships between individual genetic data and spatial landscape variables, particularly when considering local population dynamics influenced by fragmented habitats. Thus, the objective of this study was to analyze the population structure and genetic diversity of the giant anteater (Myrmecophaga tridactyla) using an individual sampling scheme (ISS) on a regional geographic scale. Data were collected from 41 specimens from twenty different locations in São Paulo State, Brazil, and six polymorphic microsatellite loci were genotyped. Our results indicate that barriers to gene flow exist and have segregated individuals of the farther away areas into two spatially structured clusters. The populations were also found to have high genetic diversity. The experimental sampling approach used herein enabled an analysis of the population dynamics of the giant anteater on a regional scale, as well as the identification of priority populations for genetic resource conservation for this species. The results reflect the need for adequate management plans. The efficacy of the sampling scheme may vary based on the study model used, but we argue that the use of an ISS combined with suitable molecular markers and statistical methods may serve as an important tool for initial analyses of threatened or vulnerable species, particularly in anthropized regions where populations are small or hard to characterize.
Keywords: Brazil; conservation genetics; giant anteater; microsatellite markers; population structure; São Paulo